Risk of hernia-related complications after transjugular intrahepatic portosystemic shunt creation in patients with pre-existing ventral abdominal hernias: 15-year experience at a quaternary medical center. Issue 1 (22nd March 2022) - McDaniel, Charles; Bell, Ruth; Farha, Natalie; Vozzo, Catherine; Bullen, Jennifer; Rosen, Michael; Romero-Marrero, Carlos; Partovi, Sasan; Kapoor, Baljendra
Abstract : Objective: Transjugular intrahepatic portosystemic shunt (TIPS) placement is used to treat the sequelae of portal hypertension, including refractory variceal bleeding, ascites and hepatic hydrothorax. However, hernia-related complications such as incarceration and small bowel obstruction can occur after TIPS placement in patients with pre-existing hernias. The aim of this study was to determine the incidence of hernia complications in the first year after TIPS placement and to identify patient characteristics leading to an increased risk of these complications. Design: This retrospective analysis included patients with pre-existing abdominal hernias who underwent primary TIPS placement with covered stents at our institution between 2004 and 2018. The 1-year hernia complication rate and the average time to complications were documented. Using a Wilcoxon rank-sum test, the characteristics of patients who developed hernia-related complications versus the characteristics of those without complications were compared. Results: A total of 167 patients with pre-existing asymptomatic abdominal hernias were included in the analysis. The most common reason for TIPS placement was refractory ascites (80.6%). A total of 36 patients (21.6%) developed hernia-related complications after TIPS placement, including 20 patients with acute complications and 16 with non-acute complications. The mean time to presentation of hernia-related complications was 66 days. Patients who developed hernia-related complications were more likely than those without complications to have liver cirrhosis secondary to alcohol consumption (p=0.049), although this association was no longer significant after multivariate analysis. Conclusion: Within 1 year after TIPS placement, approximately 20% of patients with pre-existing hernias develop hernia-related complications, typically within the first 2 months after the procedure. Patients with pre-existing hernia undergoing TIPS placement should be educated regarding the signs and symptoms of hernia-related complications, including incarceration and small bowel obstruction.